Delta-shaped anastomosis in totally laparoscopic D2 radical distal gastrectomy - Zhang, Jun (Chinese Journal of Cancer Research, 2013)
With less injury and faster postoperative recovery, laparoscopic techniques have been widely applied in D2 radical gastrectomy for distal gastric cancer. Billroth I anastomosis is a common reconstruction procedure in D2 radical gastrectomy for distal gastric cancer. The delta-shaped anastomosis, an intra-abdominal Billroth I reconstruction, has been increasingly applied by gastrointestinal surgeons. This surgical video demonstrates the delta-shaped anastomosis in laparoscopic-assisted D2 radical gastrectomy for distal gastric cancer.